2014
DOI: 10.3354/esr00613
|View full text |Cite
|
Sign up to set email alerts
|

Overlooking a potential hotspot at Great Barrier Island for the nationally endangered bottlenose dolphin of New Zealand

Abstract: Conservation initiatives are typically constrained by economic circumstances, a factor certainly true for marine mammal conservation in New Zealand. Most research in this field has been conducted following concerns over anthropogenic impacts on populations and has therefore been funded and/or driven by stakeholder interest. Bottlenose dolphins Tursiops truncatus are classified as 'Nationally Endangered' in New Zealand waters. Here, we present the first study on occurrence, site fidelity and abundance of this s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 59 publications
1
15
0
Order By: Relevance
“…Our results further show that the home ranges of the oceanic and coastal ecotypes overlap, with over a third of the encounters described in this study observed within 5 km from shore and in areas that are routinely used by the coastal ecotype, e.g., BOI (Constantine, 2002;Tezanos-Pinto et al, 2013) and HG (Berghan et al, 2008;Dwyer et al, 2014). Our findings reveal that, at least in those areas, some interactions between the two ecotypes occur.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…Our results further show that the home ranges of the oceanic and coastal ecotypes overlap, with over a third of the encounters described in this study observed within 5 km from shore and in areas that are routinely used by the coastal ecotype, e.g., BOI (Constantine, 2002;Tezanos-Pinto et al, 2013) and HG (Berghan et al, 2008;Dwyer et al, 2014). Our findings reveal that, at least in those areas, some interactions between the two ecotypes occur.…”
Section: Discussionsupporting
confidence: 74%
“…Overall, the total number of photo-identified individuals and the results on discovery rates suggest that the oceanic bottlenose dolphin population is likely significantly larger than what is documented herein. This contrasts with the coastal bottlenose dolphins, for which large numbers of previously unidentified individuals are not typically found after up to 20 years of observations (e.g., Constantine, 2002;Dwyer et al, 2014;Tezanos-Pinto et al, 2013) and corresponds with a much smaller estimated population size of~250 mature individuals for the northeastern North Island area (Baker et al, 2019).…”
Section: Rate Of Discoverymentioning
confidence: 91%
“…) and studies showing new areas with high dolphin encounter rates that were previously under‐reported (Berghan et al . ; Dwyer et al ., ). We also recommend improved documentation of stranded and beachcast dolphins and retrieving of carcasses to determine causes of mortality.…”
Section: Resultsmentioning
confidence: 97%
“…The decline in abundance (Tezanos-Pinto et al 2013) and high calf mortality are of concern and highlight the need for continued monitoring of this population. Further, other areas along the range of the northeastern North Island bottlenose dolphin population should be monitored given the shift in home ranges observed in the Bay of Islands (Tezanos-Pinto 2009, Hartel et al 2014) and studies showing new areas with high dolphin encounter rates that were previously under-reported (Berghan et al 2008;Dwyer et al, 2014b). We also recommend improved documentation of stranded and beachcast dolphins and retrieving of carcasses to determine causes of mortality.…”
Section: Resultsmentioning
confidence: 99%
“…), which may reveal changes in environmental conditions or seasonal behavioral patterns (Dwyer et al . ), reducing the bias in the estimated survival parameters (Peñaloza et al . ).…”
mentioning
confidence: 99%